Secure communications based on the synchronization of the New Lorenz-like attractor circuit - Mustafa, Mamat; Fatma Susilawati, Mohamad; Aceng, Sambas (HIKARI Ltd., 2015)
Synchronization of chaotic systems is important because it might be useful in some type of private communications. In this paper, the phenomenon of Chaos that produced in the case of autonomous New Lorenz-like attractor circuit, have been studied extensively. The initial study of this work also includes some of the most well-known tools of nonlinear dynamics, such as the Lyapunov exponents and the Poincaré map. Furthermore, the use of this type of chaotic circuit in the connection substitution synchronization method is presented in details. After conducting the analysis of the proposed synchronization scheme, the use of such an autonomous chaotic circuit as a signal modulation in secure communication systems, has been examined. Finally, numerical simulations by using MATLAB 380 Aceng Sambas et al. 2010, as well as implementation of circuit simulations by using MultiSIM 10.0, has been performed in this work.